Molecular and histological characterization of age spots. Issue 3 (9th February 2017) - Choi, Wonseon; Yin, Lanlan; Smuda, Christoph; Batzer, Jan; Hearing, Vincent J.; Kolbe, Ludger
Abstract: Age spots, also called solar lentigines and lentigo senilis, are light brown to black pigmented lesions of various sizes that typically develop in chronically sun‐exposed skin. It is well known that age spots are strongly related to chronic sun exposure and are associated with photodamage and an increased risk for skin cancer; however, the mechanisms underlying their development remain poorly understood. We used immunohistochemical analysis and microarray analysis to investigate the processes involved in their formation, focusing on specific markers associated with the functions and proliferation of melanocytes and keratinocytes. A total of 193 genes were differentially expressed in age spots, but melanocyte pigment genes were not among them. The increased expression of keratins 5 and 10, markers of basal and suprabasal keratinocytes, respectively, in age spots suggests that the increased proliferation of basal keratinocytes combined with the decreased turnover of suprabasal keratinocytes leads to the exaggerated formation of rete ridges in lesional epidermis which in turn disrupts the normal processing of melanin upwards from the basal layer. Based on our results, we propose a model for the development of age spots that explains the accumulation of melanin and the development of extensive rete ridges in those hyperpigmented lesions.